Macroeconomic determinants of external debt in Nepal: The ARDL Approach (Quest Journal of Management and Social Sciences, 2020)
Background: External debt is the loan amount borrowed from the international level, payable with interest and principal. It is the major source of financing budget deficit in a developing country. Debt accumulation for productive investment is a viable strategy for long-term development. To escape the external debt burden or for the external debt burden strategy, it is crucial to study the major macroeconomic determinants of external debt.Objective: The principal objective of this study is to examine the major macroeconomic determinants of external debt in Nepal. Methods: In this study, the external loan is taken as a dependent variable whereas, budget deficit, per capita gross domestic product, terms of trade, trade openness, foreign aid, and real effective exchange rates are taken as explanatory variables that may cause external borrowing in Nepal. The study applies the ARDL cointegration approach to trace out the relationship between the stated variables. The bound test (F-Version) has been applied for the determination of the existence of long-term cointegration among variables.Short-run dynamics is measured by the Error Correction Mechanism.Results: The empirical result indicates that fiscal deficit, trade openness, and foreign aid are major macroeconomic determinants of external debt in Nepal. From the obtained results, it is seen that an increase in foreign aid helps to significantly reduce external debt but trade openness and the budget deficit significantly leads to an increase in external debt both in the short-run as well as in the long-run. The error correction term is found to be significant and negative, showing proof of a strong association between the selected variable and ensures the correction of short-term disequilibrium to a stable equilibrium at the rate of 37 percent per annum.Conclusions: The study concludes that foreign aid, budget deficit, and trade openness are the main determinants of external debt in Nepal in both the long-run and short-run.  Appropriate export-import or foreign trade policy, effective demand management policy, progressive tax system as well as monitoring tax evasion, effectual and productive utilization of available resources helps to reduce debt accumulation and saves the nation from the possible debt trap.